Theology in the face of transhumanism - Oviedo, Lluis (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
In this writing two theological models are at stake: one is more in tune with the theologies of the incarnation that identify everything that is good as related to God or that participates in the divine; the other is rooted in a theology of redemption and feels that most human and social realities are corrupted and need to be rescued and restored, only supernaturally. The duality described justifies an inevitable pluralism and a discernment that cannot be completed a priori, since it depends deeply on the beliefs and values that are harbored. Perhaps we should assume a «wait and see» attitude and rely more on the results, to judge after evaluating to what extent a development clearly reflects God’s plan or deviates definitively from it. For this reason, I do not think that the best theological approach is one that draws «red lines» and rejects any development in that field, but at the same time that does not justify an easy and naive attitude towards those attempts, which could bring —despite of his apparent goodwill— catastrophic consequences. Theology can illustrate the way and offer good criteria, but it can hardly help to make the necessary decisions or establish a course of action in an irrefutable way. Theology has the right to be wrong and the duty to evaluate its mistakes and correct them.
Keywords: human beings; destitution; self-improvement; co-creation; sin; failed creature; salvation by grace